2018
DOI: 10.1002/slct.201800839
|View full text |Cite
|
Sign up to set email alerts
|

Condition‐Based Selective Synthesis of 3,4,5‐Trisubstituted Isoxazoline Noxides, 4,5‐Dihydroisoxazoles and Isoxazoles

Abstract: Functionalized isoxazoline N-oxides, 4,5-dihydroisoxazoles and isoxazoles have attracted considerable attention because of their wide applications. Starting from 1,1-dimethoxy-2-nitroethene and aldehydes, a cascade approach to these heterocycles was explored to achieve structural diversity controlled by different reaction conditions. Furthermore, this new protocol provided a direct access to 4-substituted-3,5-bis(methoxycarbonyl)-4,5-dihydroisoxazoles from aromatic aldehydes for the first time.[a] X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…There have been several studies of the formation of isoxazoline N -oxides from α-nitro-α,β-unsaturated esters with C–H acids such as secondary nitroalkane [ 15 ], (ethoxycarbonylmethyl)dimethylsulfonium salt [ 16 ], (ethoxycarbonylmethyl)ammonium salt [ 17 ], (ethoxycarbonylmethyl)pyridinium salt [ 18 ], α-halomalonate [ 19 ], and α-iodo aldehyde [ 20 ]. β,β-Dimethoxynitroethene is also usable as a nucleophile in this protocol [ 21 ]. Among these, only two methods employ a nitro group as a leaving group [ 15 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies of the formation of isoxazoline N -oxides from α-nitro-α,β-unsaturated esters with C–H acids such as secondary nitroalkane [ 15 ], (ethoxycarbonylmethyl)dimethylsulfonium salt [ 16 ], (ethoxycarbonylmethyl)ammonium salt [ 17 ], (ethoxycarbonylmethyl)pyridinium salt [ 18 ], α-halomalonate [ 19 ], and α-iodo aldehyde [ 20 ]. β,β-Dimethoxynitroethene is also usable as a nucleophile in this protocol [ 21 ]. Among these, only two methods employ a nitro group as a leaving group [ 15 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…β,β-Dimethoxynitroethene is also usable as a nucleophile in this protocol [ 21 ]. Among these, only two methods employ a nitro group as a leaving group [ 15 , 21 ]. In these reactions, the nucleophilicity of the nitronate ion is relatively high.…”
Section: Resultsmentioning
confidence: 99%
“…However, no general strategy can be used to afford the functionalized nitro precursors. Thus, intermolecular connection synthesis strategies have been developed, and there are two main types: (1) formal [3 + 2] cascade approaches and (2) formal [4 + 1] annulation approaches . In addition, it is reported that β-hydroxy ketoximes can be candidates to generate isoxazoline N -oxides, which undergo an intramolecular N–O coupling process by some additive oxidants .…”
mentioning
confidence: 99%